Biodiversity loss threatens human well-being. - Díaz, Sandra Myrna (2006)
The diversity of life on Earth is dramatically affected by Human alterations of ecosystems. Compelling evidence now shows that the reverse is also true: biodiversity in the broad snsse affects the properties of ecosystem and, therefore, the benefits that humans obtain from them. In this article, we provide a synthesis of the most crucial messages emerging from the latest scientific literature and international assessments of the role of biodiversity in ecosystem services and human well- being. Human societies have beeb built on biodiversity. Many activities indispensable for human subsistence lead to biodiversity loss, and this trend is ikely to continue in the future. We clearly benefit from the diversity of organisms that we have learned to use for medicines, food, fibers, and other renwable resources. In addition, biodiversity has always been an integral part of the human experience and there are many moral reasons to preserve it for its own sake. What has been less recognized is that biodiversity also influences human well- being, including the access to water and basic materials for a satifactory life, and security in the face of environmental change, through its effects on the ecosystem processes that lie at the core of the Earth´s most vital life support system.